PENGARUH KUALITAS PELAYANAN MELALUI KEPUASAN NASABAH TERHADAP LOYALITAS NASABAH PADA PT BPR SARASWATI EKABUMI - Dewa Ayu Putu Febriyanti; Ni Wayan Eka Mitariani; I Gusti Ayu Imbayani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
The rural banks industry occupies a very important role in the economic sector, especially in supporting the development of small and medium enterprises. The more intense competition among rural banks, the services that rural banks provide must be more optimal so that the company is able to win the competition. The purpose of this study is to determine the effect of service quality on customer satisfaction and loyalty at PT BPR Saraswati Ekabumi in Badung regency. Respondents in this research are credit, deposit and savings customers in BPR Saraswati Ekabumi. The number of respondents in this study was determined 124 respondents by using accidental sampling technique.This study uses Partial Least Square (PLS) analysis with the help of Smart PLS 3.0 program.The results of this study indicate that: 1) the quality of service has a positive and significant impact on customer satisfaction, 2) satisfaction has positive and significant effect on customer loyalty, 3) service quality has positive and significant influence to customer loyalty.